Effects of heavy metals on bacterial growth parameters in degradation of phenol by an Antarctic bacterial consortium - Tengku-Mazuki, Tengku Athirrah; Darham, Syazani; Convey, Peter; Shaharuddin, Noor Azmi; Zulkharnain, Azham; Abdul Khalil, Khalilah; Mohd Zahri, Khadijah Nabilah; Subramaniam, Kavilasni; Merican, Faradina; Gomez-Fuentes, Claudio; Ahmad, Siti Aqlima (Sociedade Brasileira de Microbiologia,Brazilian Society for Microbiology, 2023)
Antarctica has often been perceived as a pristine continent until the recent few decades as pollutants have been observed accruing in the Antarctic environment. Irresponsible human activities such as accidental oil spills, waste incineration and sewage disposal are among the primary anthropogenic sources of heavy metal contaminants in Antarctica. Natural sources including animal excrement, volcanism and geological weathering also contribute to the increase of heavy metals in the ecosystem. A microbial growth model is presented for the growth of a bacterial cell consortium used in the biodegradation of phenol in media containing different metal ions, namely arsenic (As), cadmium (Cd), aluminium (Al), nickel (Ni), silver (Ag), lead (Pb) and cobalt (Co). Bacterial growth was inhibited by these ions in the rank order of Al < As < Co < Pb < Ni < Cd < Ag. Greatest bacterial growth occurred in 1 ppm Al achieving an OD600 of 0.985 and lowest in 1 ppm Ag with an OD600 of 0.090. At a concentration of 1.0 ppm, Ag had a considerable effect on the bacterial consortium, inhibiting the degradation of phenol, whereas this concentration of the other metal ions tested had no effect on degradation. The biokinetic growth model developed supports the suitability of the bacterial consortium for use in phenol degradation.